TINGKAT KELINCAHAN SHUTTLE RUN SISWI EKSTRAKURIKULER BOLA BASKET BERDASARKAN HASIL TES SHUTTLE RUN SMKN 2 KOTA KEDIRI TAHUN 2024 - Aprillia, Shielsila; Rizky, Muhammad Yanuar; Himawanto, Wasis (Fakultas Ilmu Keolahragaan Unimed, 2025)
The objective of this study is to assess the agility level of female students at SMKN 2 Kota Kediri who participate in basketball extracurricular activities. The assessment will be conducted using a 4x10 meter shuttle run test. The impetus for this study stems from the preliminary findings that the agility of female students is still below average. The approach employed in this study is quantitative, with a survey method being utilized to collect the necessary data. The results from 24 data points show a minimum value of 16.10 seconds, a maximum of 21.95 seconds, an average of 17.93 seconds, and a standard deviation of 1.64. The analysis revealed that 29.2% of female students were in the